Brown fat thermogenesis and cold adaptation in humans - Takeshi Yoneshiro; Mami Matsushita; Juro Sakai; Masayuki Saito (Journal of Physiological Anthropology)
Abstract Brown adipose tissue (BAT) is a site of non-shivering thermogenesis (NST) in mammals. Since the rediscovery of BAT in adult humans, there has been a remarkable advance in human BAT researches, revealing the significant roles of this thermogenic tissue in cold-induced NST and cold adaptation. Cold stress influences BAT in various time spans: acute cold exposure promptly activates BAT to induce NST, which contributes to immediate maintenance of body temperature. Prolonged cold exposure recruits BAT, resulting in increased capacity of NST and improved cold tolerance. Such BAT adaptation not only occurs in the exposed individual but also is passed on to the next generation, probably via the paternal lineage. As such, BAT plays a role in acute, chronic, and transgenerational adaptation to cold environment in humans.